THE USE OF INULIN AND SOY PROTEIN ISOLATE IN PRODUCING HARD-DOUGH BISCUITS FOR SENIOR PEOPLE - Antonella DOROHOVYCH (Stefan cel Mare University of Suceava, 2017)
The article reviews the potential rationale of the addition of inulin and soy proteins to harddough biscuits recommended for senior people’s diet. Hard-dough biscuits were considered as the objects of this nutritional enrichment since they have an optimal balance of proteins, fats and carbohydrates compared to the rest of flour-baked foods. Our study aimed to examine the role that inulin and protein play in the technological processes associated with producing hard-dough biscuits; in particular, special consideration was given to the selection of the optimal proportion of the new raw components, as well as the effect they cause on the quality of the hard-dough biscuits, the emulsion and the dough. The study identifies the role that inulin and soy protein isolate play in the heat treatment processes and storage of hard-dough biscuits intended for senior people. Recommendations have been given as to the healthy diet for senior people.The authors have proved a significant effect of the new raw materials on the structural and mechanical characteristics of dough that assumes additional elasticity due to the increase in the volume of bound moisture in the hydrated flour. It has been established that the addition of inulin and soy isolate prolongs the duration of the heat treatment of hard-dough biscuits. By consuming 100 g of special-purpose hard-dough biscuits, it is possible to fill up to 30% of the daily need for fiber in humans. The study has proved the advisability of using soy protein isolate and inulin when producing special-purpose hard-dough biscuits for senior people because of its enrichment with complete proteins, irreplaceable amino acids and food fibers.